"Lembaran Cinta Mama” terhadap pertumbuhan dan perkembangan anak usia 0-24 Bulan - Deisye M. D. Pesik; Senny Rondonuwu (JIDAN (Jurnal Ilmiah Bidan), 2022)
Background : The first 1000 days of life (1000 HPK) consists of 270 days during pregnancy and 730 days in the first two years of a baby's life. The impact of the golden period will greatly affect the growth and development of the baby until adulthood. The first thousand days of life are: 270 days in the womb and 730 days during the first 2 years after birth. Purpose: this research is to analyze the effect of using "Mama's Love Sheet" on the growth and development of children aged 0-24 months. Methods: This study used a quasi-experimental design with a two group posttest design. Results : there were significant differences in birth weight, birth length and child development between the intervention and control groups with a p value of 0.05. There are significant differences in body weight, birth length and baby development. Mama's Love Sheet (LCM) has an influence on children's weight growth in the first 1000 days of life. Recommendations for pregnant women, nursing mothers and mothers with children aged 0-24 months can use the Mama's Love Sheet together with the MCH handbook.